ON ENTIRE FUNCTIONS WITH GIVEN ASYMPTOTIC BEHAVIOR - Isaev K . P . (Проблемы анализа, 2018)
We study approximation of subharmonic functions on the complex plane by logarithms of moduli of entire functions. In the theory of series of exponentials these entire functions are the main tool. In questions of decomposition of functions into a series of exponentials, the subharmonic function, as a rule, satisfies the Lipschitz condition. We prove the theorem on approximation of such subharmonic functions. Also we prove the theorem on joint approximation of two subharmonic functions.